2001
DOI: 10.1142/s0217751x0100550x
|View full text |Cite
|
Sign up to set email alerts
|

SOLVABILITY OF THE F4 INTEGRABLE SYSTEM

Abstract: It is shown that the F 4 rational and trigonometric integrable systems are exactlysolvable for arbitrary values of the coupling constants. Their spectra are found explicitly while eigenfunctions by pure algebraic means. For both systems new variables are introduced in which the Hamiltonian has an algebraic form being also (block)triangular. These variables are invariant with respect to the Weyl group of F 4 root system and can be obtained by averaging over an orbit of the Weyl group. Alternative way of finding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(73 citation statements)
references
References 17 publications
3
70
0
Order By: Relevance
“…It implies that the coefficient functions in front of the second derivatives in the Laplace-Beltrami operator are polynomials in invariants of the Weyl group. This result was rediscovered (and then generalized) later in [4], [5], [6] and [8] for A n , BC n , G 2 and F 4 algebras, respectively. It was shown that the algebraic structure persists for the whole Laplace-Beltrami operator: the coefficient functions in front of the first derivatives are polynomials as well.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…It implies that the coefficient functions in front of the second derivatives in the Laplace-Beltrami operator are polynomials in invariants of the Weyl group. This result was rediscovered (and then generalized) later in [4], [5], [6] and [8] for A n , BC n , G 2 and F 4 algebras, respectively. It was shown that the algebraic structure persists for the whole Laplace-Beltrami operator: the coefficient functions in front of the first derivatives are polynomials as well.…”
Section: Introductionmentioning
confidence: 90%
“…The Hamiltonian of the rational F 4 model written in the basis of the standard F 4 roots has the form (see [8] 8 ),…”
Section: The Rational G 2 Modelmentioning
confidence: 99%
See 3 more Smart Citations